An Outline of the Early Christian Political Philosophy - Sáry, Pál (2025)
In the works of the Christian writers living in the Roman Empire, we can read in many places about the necessity of state power, the advantages of the monarchical system of rule and imperial unity, the special relationship between God and the ruler, the most important tasks of the emperor, the theoretical questions of the relationship between the state and the church, the manifestations of state violence, the limits of political power, the importance of private property, the duties of subjects and their right to resist. By examining these topics, the book aims to provide an introduction to the world of early Christian political ideas. The work also tries to reveal what political ideas Christianity adopted from previous cultures, and what the followers of Christ created new in the field of political philosophy.